2017
DOI: 10.31254/jmr.2017.3313
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and awareness of Hypertension among urban and rural Adults in the Keta Municipality, Ghana

Abstract: Background: With the changing trends in the epidemiology of hypertension (HPT), recent studies have shown an increasing prevalence of HPT in rural than urban communities. This study examined the prevalence of HPT and its awareness among urban and ruraladults in Keta Municipality. Method: A population-based cross-sectional study involving 264 adults (18-65 years). Face-to-face interview using semi-structured questionnaire was used to collect information. Blood pressure and anthropometric measurements were taken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…In 17 (20.0%) studies, the prevalence of hypertension was based on the measured BP≥ 140/90 mmHg as well as on or a history of previous diagnosis of hypertension by a health professional [ 49 , 50 , 72 , 76 , 80 , 117 ] or on a history of current anti-hypertensive medication [ 43 , 59 , 62 , 68 , 71 – 74 , 87 , 91 , 94 , 98 ]. Six (7.1%) studies, five of them conducted by the same research team, excluded participants with a history of hypertension, diabetes, coronary heart disease or those on anti-hypertensive or cholesterol-lowering medication use [ 54 , 65 , 67 , 69 , 109 , 125 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 17 (20.0%) studies, the prevalence of hypertension was based on the measured BP≥ 140/90 mmHg as well as on or a history of previous diagnosis of hypertension by a health professional [ 49 , 50 , 72 , 76 , 80 , 117 ] or on a history of current anti-hypertensive medication [ 43 , 59 , 62 , 68 , 71 – 74 , 87 , 91 , 94 , 98 ]. Six (7.1%) studies, five of them conducted by the same research team, excluded participants with a history of hypertension, diabetes, coronary heart disease or those on anti-hypertensive or cholesterol-lowering medication use [ 54 , 65 , 67 , 69 , 109 , 125 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the study with the highest prevalence, 38% of the participants had previously been diagnosed with hypertension. In 51 and 50 individual studies respectively, the prevalence ranged from 2.8% [ 90 ] to 58.3% [ 72 ] in men and from 1.0% [ 122 ] to 90.0% [ 60 ] in women.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Incoom et al reported a prevalence of 25.4% among adults in the Hohoe Municipality of Ghana [21]. Similarly, Atinyi et al, in a study among adults in Keta Municipality of Ghana, reported a prevalence of 27.3% [22]. Another study by Bani et al among traders in Hohoe Municipality, Ghana, reported a prevalence of 33.8% [23].…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies exploring the prevalence of NCDs, e.g. hypertension in various Ghanaian populations [74][75][76][77], but, to our knowledge, there are no studies looking at the incidence of NCDs. This would require a large-scale cohort study and it could consider the main NCDs and comorbidities of interest in Ghana, i.e.…”
Section: Implications For Policy and Practicementioning
confidence: 99%